2004
DOI: 10.1111/j.1755-6988.2004.tb00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Treating Substance‐Abusing Parents: A Study of the Pima County Family Drug Court Approach

Abstract: A geographical comparison‐group design was used to examine the effectiveness of the Pima County (Arizona) Court Assisted Treatment Services (CATS) program and its drug court intervention. The study compared the summary statistics for the volunteers to the family drug court (n=33) with a treatment‐refusal group (n=42) and a treatment‐as‐usual group (n=45) from a matched geographical area. The findings of this study indicate that the family drug court group had higher engagement and completion rates of residenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 8 publications
1
39
1
Order By: Relevance
“…Of the two, there is more evidence that FDTCs increase reunification rates; nine studies found an increase in reunification for participants (Ashford, 2004;Boles, Young, Moore, & DiPirro-Beard, 2007;Burrus, Mackin, & Finigan, 2011;Chuang, Moore, Barrett, & Young, 2012;Dakof et al, 2010;Gifford, Eldred, Vernerey, & Sloan, 2014;Green, Furrer, Worcel, Burrus, & Finigan, 2009;Green, Rockhill, & Furrer, 2007b;Worcel, Furrer, Green, Burrus, & Finigan, 2008). Several studies found reduced time spent in foster care for children of participants (Bruns, Pullmann, Weathers, Wirschem, & Murphy, 2012;Burrus et al, 2011;Gifford et al, 2014;Green, Furrer, Worcel, Burrus, & Finigan, 2007a;Worcel et al, 2008), although one study reported longer stays (Chuang et al, 2012) and another found the effect varied by court (Green et al, 2009).…”
Section: Family Drug Treatment Courtsmentioning
confidence: 99%
“…Of the two, there is more evidence that FDTCs increase reunification rates; nine studies found an increase in reunification for participants (Ashford, 2004;Boles, Young, Moore, & DiPirro-Beard, 2007;Burrus, Mackin, & Finigan, 2011;Chuang, Moore, Barrett, & Young, 2012;Dakof et al, 2010;Gifford, Eldred, Vernerey, & Sloan, 2014;Green, Furrer, Worcel, Burrus, & Finigan, 2009;Green, Rockhill, & Furrer, 2007b;Worcel, Furrer, Green, Burrus, & Finigan, 2008). Several studies found reduced time spent in foster care for children of participants (Bruns, Pullmann, Weathers, Wirschem, & Murphy, 2012;Burrus et al, 2011;Gifford et al, 2014;Green, Furrer, Worcel, Burrus, & Finigan, 2007a;Worcel et al, 2008), although one study reported longer stays (Chuang et al, 2012) and another found the effect varied by court (Green et al, 2009).…”
Section: Family Drug Treatment Courtsmentioning
confidence: 99%
“…Another limitation of prior studies is their limited geographic scope. For example, using data from a single county study, Ashford (2004) reported that the children of parents who participated in a family drug court program received a permanency decision sooner and were more likely to be reunified with their families than children of parents who either refused treatment or participated in the ''treatment as usual'' group. A study using data from a single city documented that children of families in a family drug court had a mean stay in foster care of 50 days less than the comparison group and were more likely to be reunified with their parents (Burrus, Making, and Finigan 2011).…”
Section: Family Dtcsmentioning
confidence: 99%
“…The family drug court (FDC) approach is a procedural innovation in child welfare that is used in many jurisdictions to address parental alcohol and other drug abuse problems (Ashford, 2004;Young, 2003;Young, Gardner, & Dennis, 1998). A national survey of professionals employed in child welfare found that nearly 80% of the respondents said that "substance abuse causes or exacerbates most cases of child abuse that they face" (National Center on Addiction and Substance Abuse [CASA], 1999, p. ii).…”
mentioning
confidence: 99%
“…Although many jurisdictions have created FDCs, the elements required to validly implement this approach have been subjected to minimal empirical scrutiny (Ashford, 2004). A key assumption in most FDCs is that compliance with court orders for substance abuse treatment will increase because parents have to appear weekly before a judge (Edwards, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation